Recognizing employees’ contribution to effectiveness and values: A randomized waitlist-controlled trial of operant-based leadership training - Martin Grill (PLoS ONE, 2025)
To develop and sustain a healthy and efficient work environment, managers need to provide their employees with relevant and useful performance feedback. However, research on leadership training in functional behaviors, such as performance feedback, has yet to demonstrate consistent long-term effectiveness. Therefore, the purpose of this study was to evaluate the long-term influence of operant-based leadership training on managers’ performance feedback behaviors. Municipality employees (n = 439) responded to a questionnaire four times over a period of 18 months. The employees’ managers were randomized into an experimental and a control group. The managers in the experimental group received managerial behavioral training, while the waitlist control group managers did not. Multilevel growth curve modeling was used for data analysis. The results showed that employees in the experimental group reported a significantly greater improvement in their managers’ performance feedback behaviors compared to employees in the control group (β = 0.30, p = 0.04). Furthermore, the improvement in the experimental group managers’ leadership behaviors had a linear trajectory throughout the 18-month study period, with no significant deceleration in their learning curve (Δχ2(2) = 2.2, p = 0.34). In conclusion, operant-based leadership training can help managers develop their performance feedback behaviors and the effect of such training is persistent over time. The findings imply that leadership training research and practice should strive to integrate operant learning theory and practice in order to improve the long-term effectiveness of leadership training interventions. Positive utility reactions, achieved by shaping leadership behaviors to optimize their fit with the managers’ work context, may be critical for ensuring the enduring effects of leadership training.